ANTIOXIDANT ACTIVITY FROM TEN SPECIES OF MYRTACEAE - Ramadhania, Zelika Mega; Insanu, Muhamad; Gunarti, Neni Sri; Wirasutisna, Komar Ruslan; Sukrasno, Sukrasno; Hartati, Rika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Antioxidants are compounds that can inhibit free radical reactivity. They become very interesting to be observed because they can prevent some diseases like goat arthritis, cancer, cardiovascular disease, Alzheimer's disease, macular degeneration etc. Since Indonesia is rich for its biodiversity, there are a lot of plants that have potential to be developed as new alternative antioxidants. The aim of this research was to evaluate antioxidant activity from ten species of myrtaceae (Syzygium cumini, S. samarangense, S. aqueum, S. aromaticum, S. polyantum, S. jambos, S. malaccense, Psidium guajava, Eucalyptus deglupta and Melaleuca leucadendra). Methods:Continuous extraction with Soxhlet apparatus was selected as extraction method. Three solvents (n-hexane, ethyl acetate and methanol) with different polarity were used in this process. DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity were used to evaluate antioxidant activity with ascorbic acid as a standard drug. Results:Based on the experiments, methanol extracts showed higher activity than other extracts with their IC50was below than 25 µg/ml.The lowest IC50 was exhibited by methanol extract of S. jambos, which was 7.8 µg/ml. Conclusion:It can be concluded that S. jambos is potential to be developed as a new alternative antioxidant.